Panmen's Musical Penmanship - Blood, Peter Ray (Express)
In this article, Ray Holman, despite being criticized for the revolutionary move of penning his own composition, "steelband calypso" for Panorama, has continued to compose and arrange 'customised' Panorama music. Holman's mentor, Len 'Boogsie' Sharpe, also started taking on the task of composing his own songs and was fully supported by his band Phase II Pan Groove. This year there was a larger than ever collection of 'exclusive pan calypsoes'.
Keywords: Arrangers (Musicians) -- Trinidad and Tobago; Steel bands (Music) -- Trinidad and Tobago; Music -- Performance -- Trinidad and Tobago; Steel band music -- Trinidad and Tobago